MELIRIK IKAN NILA DALAM SISI EKONOMI KREATIF PADA KOMUNITAS PEMUDA DESA GELAM JAYA KABUPATEN TANGERANG - Sonny Santosa (Journal MISSY (Management and Business Strategy), 2021)
This research is motivated by the phenomenon of the Covid-19 Pandemic which has almost hit all nations in the world and has caused a domino effect on the joints of human life itself. Various fields experience tidal effects, including one of them is the economic sector. To deal with uncertain situations and ups and downs like today that can make a country enter the trough of an economic crisis, it is necessary to have support from the central government to the regions to jointly generate the economy. Therefore, this study aims to analyze the factors that influence the interest of the youth community of Gelam Jaya Village to contribute to developing tilapia fish farming which aims to increase the original income of the environment so as to be able to make choices for the community to continue to get income distribution. The problem in this research is the low interest of the youth community to take part in creative economic efforts for the surrounding environment. In this study, a research model was proposed to analyze the interest of young people in actively contributing to tilapia cultivation, where from the location side, Gelam Jaya Village made it possible to develop collaboration with related agencies in terms of generating the creative economy. This study examines the factors that can be obtained when interviewing the village regarding the youth's interest in contributing to the creative economy. This study uses answers from 169 respondents who were sampled. The data analysis tool used is factor analysis in the SPSS v.18 program. The results of data analysis show that the Situational Involvement (X1) factor of 0.766 is one of the most dominating factors for respondents in actively contributing to developing tilapia cultivation in Gelam Jaya Village, and has a value above 0.50.